A reinserção do policial civil aposentado no mercado de trabalho em Santana do Livramento - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This study sought to analyze the perception of dispossessed civilian police regarding their reintegration into the labor market in Santana do Livramento. In order to obtain the results, a qualitative research was conducted, with structured questions in an online group of a social network of great access and use. Survey respondents were six former civil police officers who returned to work. The results of the study indicated that, from the perception of these detached police officers, of the six reinserted, four are working in the law area, in law firms and one case acting directly as a lawyer. One is a security professional and another works as a bank clerk for a bookmaker. The two most cited reasons for reintegration into work were the need to have an income that was equivalent to the old standard of living they had before retiring, and the sense of usefulness, since without revealing that they are still able to contribute to society. with their knowledge and experience gained throughout their careers. Finally, it was identified that there are still few programs or incentives for reintegration of the elderly in the Santana labor market.
The reintegration of the retired civil police officer into the labor market in Santana do Livramento
Keywords: Reinserção profissional; Policial civil; Desaposentadoria; Professional reinsertion; Civil police; Dismissal; CNPQ::CIENCIAS SOCIAIS APLICADAS